Endosome-based protein trafficking and Ca2+ homeostasis in the heart - Curran, Jerry; Makara, Michael A.; Mohler, Peter J. (Frontiers in Physiology, 2015)
The ability to dynamically regulate, traffic, retain, and recycle proteins within the cell membrane is fundamental to life and central to the normal function of the heart. In the cardiomyocyte, these pathways are essential for the regulation of Ca2+, both at the level of the plasma membrane, but also in local cellular domains. One intracellular pathway often overlooked in relation to cardiovascular Ca2+ regulation and signaling is the endosome-based trafficking pathway. Highlighting its importance, this system and its molecular components are evolutionarily conserved across all metazoans. However, remarkably little is known of how endosome-based protein trafficking and recycling functions within mammalian cells systems, especially in the heart. As the endosomal system acts to regulate the expression and localization of membrane proteins central for cardiac Ca2+ regulation, understanding the in vivo function of this system in the heart is critical. This review will focus on endosome-based protein trafficking in the heart in both health and disease with special emphasis for the role of endocytic regulatory proteins, C-terminal Eps15 homology domain-containing proteins (EHDs).